Application of high-resolution ultrasound, real-time elastography, and contrast-enhanced ultrasound in differentiating solid thyroid nodules. Issue 45 (November 2016) - Zhang, Yu-Zhi; Xu, Ting; Gong, Hai-Yan; Li, Cui-Ying; Ye, Xin-Hua; Lin, Hong-Jun; Shen, Mei-Ping; Duan, Yu; Yang, Tao; Wu, Xiao-Hong
Abstract : Abstract: High-resolution ultrasound (HRUS) is a sensitive tool for identifying thyroid nodules. Real-time elastography (RTE) and contrast-enhanced ultrasound (CEUS) are newly developed methods which could measure tissue elasticity and perfusion features. The aim of the present study was to evaluate and compare the diagnostic efficiency of HRUS, RTE, CEUS and their combined use in the differentiation of benign and malignant solid thyroid nodules. In total, 111 consecutive patients with 145 thyroid nodules who were scheduled for surgery were included in the study. All of them underwent HRUS, RTE, and CEUS examination. The independent ultrasound (US) predictors for malignancy were determined and quantified using logistic regression analysis, based on which a risk-scoring model was established for each method. The diagnostic efficiency of each method was assessed by receiver operating characteristic (ROC) curve analysis. HRUS showed the best diagnostic efficiency among the 3 US methods, with 74.6% sensitivity and 87.8% specificity. CEUS had higher sensitivity (85.7%), whereas RTE alone did not show much advantage. Combined use of RTE and HRUS increased the sensitivity (92.1%). The HRUS-RTE-CEUS combination could increase both the sensitivity and specificity (87.3%, 91.5%), with the best AUC (0.935) among all the methods. The overall diagnostic value of HRUS in predicting malignancy is the best among the 3 US methods. Combined use of RTE and CEUS and HRUS could improve the diagnostic efficiency for solid thyroid nodules.